Critically assessing the influence of the global digital policy industrial complex on the formulation of national digital policies: a South African perspective - Camngca, Ade Ed (My University, 2021)
Overview: Using South Africa as a case study, this report explores and critically appraises the extent to which national digital policies are influenced by, or insulated from, external actors, ideas, and discourses. The research examines the intersection between global digital policy and South Africa's digital policy priorities. It has done this to better understand how the South African government has attempted to harness the developmental potential of digital technologies through specific policies. The research also considers the interplay between international and intergovernmental institutions, states of the core, epistemic communities, donors, developed nations, technology drivers (equipment and software manufacturers) multinational corporations, and the composition of the relationships between and within these institutions – the bureaucracies within them, and the alliances that exist between policy networks and institutions that might influence South Africa’s policy formulation processes. Finally, this research report demonstrates how certain institutions influence or constrain the extent to which the country’s digital policies are a product of national debate, reflection, and determination. Research Methodology: Leaning on Constructivism as a philosophical foundation, the research method prioritised the qualitative approach. The constructivist paradigm was used as a lens for analysing the responses from the interview respondents, who, through their individual experiences and reflections, have constructed their own knowledge on how the different aspects of the global digital policy industrial complex (GDPIC) operate (defined under sections 1.2.1 and 1.2.3). In addition to analysing the data obtained from interviews, the research also examined two policy documents and one discussion document to showcase textual evidence of the GDPIC’s influence on i South Africa’s digital policy formation. The documents that were analysed are the South African National Broadband Plan- SA Connect (RSA, 2013), the National Integrated ICT Policy White Paper (RSA, 2016) and Enabling South Africa 4.0 Becoming 4IR Ready: A Government Led Approach (Accenture & RSA, 2019). Key Findings: The research findings reveal that the global demands of the GDPIC have influenced two of the three documents that were examined. This has contributed to setting up the policy, and by extension, the country, for failure. Policy failure in South Africa has usually been ascribed to improper or no implementation. Less explored is the idea that South Africa’s digital policies have failed because the ideas and discourses that inform them serve the interests of the GDPIC rather than serving the country.
A research report submitted in partial fulfillment of the requirements for the Degree of Master of Art in ICT Policy and Regulation (MA ICTPR) to the Faculty of Humanities, School of Literature, Language & Media studies (SLLM), University of the Witwatersrand, 2021